Implementation of Prediction Guide Method in Islamic Religious Education Learning - Zamroji, Muhammad; Robi’ul Afif Nurul ‘Aini; Robi'ul Afif Nurul 'Aini (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
The Prediction Guide Method is a learning model designed to actively engage students from the beginning to the end of the learning process. By using this method, students are expected to be involved from the start of the session, maintain focus, and keep their attention while the teacher delivers the material. The steps in implementing this method begin with the formation of study groups by the teacher in the classroom. Through these groups, students can discuss and share their understanding of the material being taught. The key to the success of the Prediction Guide Method is creating an interactive and non-monotonous learning atmosphere. One common problem in traditional teaching methods is that they are often too rigid and static, which can cause students to quickly feel bored and lose motivation. However, by implementing the Prediction Guide Method, the teaching and learning process becomes more engaging and encourages active participation from all students. This method has a particularly significant impact on student engagement in Islamic Education. As a result, the implementation of this method not only makes students more active but also improves their comprehension and learning outcomes. Students can more easily remember and understand the material because they are directly involved in the learning process. Through this method, teachers can also better assess students’ engagement and understanding, thereby enhancing the overall quality of learning.